Discriminating Between Reorganized and Liquidated Firms in Bankruptcy. - Casey, Cornelius J.; McGee, Victor E.; StIckney, Clyde P. (The Accounting Review, 1986)
Abstract ABSTRACT: A model proposed by White [1981, 1984] for distinguishing bankrupt firms that successfully reorganize from those that liquidate is tested empirically in this study. Using probit analysis, two factors were found to have significant discriminating power: the proportion of assets not secured or pledged at the bankruptcy filing date (referred to as the free assets percentage) and the change in profitability In the years preceding bankruptcy. The probit model was able to classify accurately 69 percent of the firms in the estimation sample and 59 percent of the firms in a holdout sample.